Associations between cognitive impairment and motor dysfunction in Parkinson's disease. Issue 6 (12th May 2017) - Wang, Yi‐Xuan; Zhao, Jue; Li, Da‐Ke; Peng, Fang; Wang, Ying; Yang, Ke; Liu, Zhen‐Yang; Liu, Feng‐Tao; Wu, Jian‐Jun; Wang, Jian
Abstract: Introduction: Numerous studies have been carried out to explore the potential association between neurologic deficits and variable clinical manifestations of Parkinson's disease (PD). The aim of our study was to investigate the association between cognitive performance and motor dysfunction in Chinese patients with PD. Methods: Data from 96 patients with PD were obtained from the Parkinson's disease patient cohort database of Huashan Hospital. All participants underwent a comprehensive neuropsychological evaluation to assess cognitive status, that included scoring on the Mini‐mental state examination (MMSE), followed by more detailed cognitive assessment on five main cognitive domains (verbal memory, nonverbal memory, visuospatial function, language and attention/executive function). Correlations between cognitive and motor scores were investigated after controlling for age, disease duration, education, and gender. Results: We report a significant correlation between subdomains of cognitive impairment and motor dysfunction using analyses of the multiple linear regression. Notably, executive function and attention was significantly associated with bradykinesia and rigidity, while visuospatial function was associated with bradykinesia and tremor. Conclusions: The association between motor dysfunction and cognitive decline in PD might highlight deficits represented by a shared neurochemical pathway. Abstract : In this manuscript, we investigated the association between impairments in cognitive subdomains and motor features in 96 Chinese PD patients. Overall, executive function and attention was associated with bradykinesia and rigidity, while visuospatial function was associated with bradykinesia and tremor. Of which, the correlation between visuospatial memory reservation and tremor was not reported previously, probably reflecting the involvement of other non‐dopaminergic transmitter systems like acetylcholine underlying these functions.